Dressing‐related pain in patients with chronic wounds: an international patient perspective - Price, Patricia E (Int Wound J, 2008)
This cross‐sectional international survey assessed patients’ perceptions of their wound pain. A total of 2018 patients (57% female) from 15 different countries with a mean age of 68·6 years (SD = 15·4) participated. The wounds were categorised into ten different types with a mean wound duration of 19·6 months (SD = 51·8). For 2018 patients, 3361 dressings/compression systems were being used, with antimicrobials being reported most frequently (n= 605). Frequency of wound‐related pain was reported as 32·2%, ‘never’ or ‘rarely’, 31·1%, ‘quite often’ and 36·6%, ‘most’ or ‘all of the time’, with venous and arterial ulcers associated with more frequent pain (P= 0·002). All patients reported that ‘the wound itself’ was the most painful location (n= 1840). When asked if they experienced dressing‐related pain, 286 (14·7%) replied ‘most of the time’ and 334 (17·2%) reported pain ‘all of the time’; venous, mixed and arterial ulcers were associated with more frequent pain at dressing change (P < 0·001). Eight hundred and twelve (40·2%) patients reported that it took <1 hour for the pain to subside after a dressing change, for 449 (22·2%) it took 1–2 hours, for 192 (9·5%) it took 3–5 hours and for 154 (7·6%) patients it took more than 5 hours. Pain intensity was measured using a visual analogue scale (VAS) (0–100) giving a mean score of 44·5 (SD = 30·5, n= 1981). Of the 1141 who reported that they generally took pain relief, 21% indicated that they did not feel it was effective. Patients were asked to rate six symptoms associated with living with a chronic wound; ‘pain’ was given the highest mean score of 3·1 (n= 1898). In terms of different types of daily activities, ‘overdoing things’ was associated with the highest mean score (mean = 2·6, n= 1916). During the stages of the dressing change procedure; ‘touching/handling the wound’ was given the highest mean score of 2·9, followed by cleansing and dressing removal (n= 1944). One thousand four hundred and eighty‐five (80·15%) patients responded that they liked to be actively involved in their dressing changes, 1141 (58·15%) responded that they were concerned about the long‐term side‐effects of medication, 790 (40·3%) of patient indicated that the pain at dressing change was the worst part of living with a wound. This study adds substantially to our knowledge of how patients experience wound pain and gives us the opportunity to explore cultural differences in more detail.